Patient resistance as a resource: candidate obstacles in diabetes consultations. Issue 7 (4th June 2016) - Barton, Josh; Dew, Kevin; Dowell, Anthony; Sheridan, Nicolette; Kenealy, Timothy; Macdonald, Lindsay; Docherty, Barbara; Tester, Rachel; Raphael, Debbie; Gray, Lesley; Stubbe, Maria
Abstract: This study uses conversation analysis to explore 'candidate obstacles', a practice observed in sequences of patient resistance to lifestyle advice within health professional consultations. This article presents illustrative analyses of selected data excerpts drawn from audio‐visual recordings of 116 tracked consultations between health professionals and 34 patients newly diagnosed with type 2 diabetes mellitus in New Zealand. The analysis shows that in consultations where health promotion activities are central, patient resistance can provide space for patients to identify obstacles to their compliance with lifestyle advice. Identifying candidate obstacles provides opportunities for health professionals to align advice with concerns of patients and potentially improve patient outcomes.